Praxis e sapere tra i Grundrisse e il Capitale - Mustè, Marcello (Bollettino Filosofico, 2025)
In the pages on machines in the sixth notebook of the Grundrisse and in Chapter 13 of the first volume of Capital on «machines and modern industry» Marx develops the theory of relative surplus-value to its full extent and announces the search for the third volume on the tendency of the rate of profit to fall. The theoretical assumption underlying this analysis can be found in the “abstract” presentation of the «labour process» in Chapter 5 of the first volume of Capital, where the nature of praxis is considered «independently of any determined social form», In the comparison between the two situations – concrete labour and the system of machines – the expropriation of knowledge from the producer and the incorporation of science into capital emerge as key elements in understanding exploitation. The relationship between praxis and knowledge also defines a new level of class conflict, centred on social intellect or “general intellect”, different from the one characteristic of the era of absolute surplus-value and the struggle for the “normal working day”. Keywords: Class Struggle, Communism, General Intellect, Labour Theory, Philosophy of Praxis